(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
An image created using oil paints can compare favorably with other means of image. This is because oil paints dissolve in oil and create a smooth, consistent image that can be more robust for safety and durability. One of the important characteristics of oil paint is the ability to mix base colors, which allows artists to create an infinite number of shades. And also when mixing paints with certain substances, you can get additional different color shades and get a more effective and convenient paint texture for use on various surfaces.